Integrating Tinggihari Site Local Wisdom into History Learning: Fostering Students’ Historical Awareness - Rani Oktapiani; Citra Rafika Utari; Rudi Hermawan (Criksetra: Jurnal Pendidikan Sejarah, 2026)
History education is one of the strategic steps to foster historical awareness. However, until now, history education still carries a strong stigma of focusing solely on memorizing historical facts, with little relevance or contextual connection to today's students and the environments in which they grow up. One approach to making history education more contextual is to integrate local wisdom. This study aims to analyze the effect of integrating local wisdom from the Tinggihari Site into history learning on students' awareness and compare it with conventional textbook-based learning. The method used is a quasi-experiment with a pretest-posttest control-group design, involving four classes of students at SMA Negeri 4 Lahat, which were then divided into two research groups: two experimental classes and two control classes. Data analysis in this study was conducted using statistical tests, namely the Wilcoxon, Mann-Whitney, and N-Gain tests. The results showed a significant increase in the experimental class (Asymp. Sig = 0.000 < 0.05) with an N-Gain of 0.38 (moderate), while the control class showed a decrease with an N-Gain of -0.17 (low). The Mann–Whitney test showed a significant difference between the two groups (Asymp. Sig = 0.000 < 0.05). The results of this study demonstrate that integrating local wisdom from the Tinggihari Site can enhance students' historical awareness across cognitive, affective, and moral domains. This research suggests that history learning can be an effective strategy for strengthening national identity and character.